Policy Perspectives on State Elementary and Secondary Public Education Finance Systems in the United States - Deborah A. Verstegen (Educational Considerations, 2016)
The purpose of this article is to describe and compare individual state funding systems for public elementary and secondary education in the United States.
Keywords: Methodology; elementary and secondary education; Funding Systems; Foundation program; Two-Tiered Funding Systems; Foundation Programs; transportation